The effect of neurologic music therapy in patients with cerebral palsy: A systematic narrative review - Yang, Seoyon; Suh, Jee Hyun; Kwon, SuYeon; Chang, Min Cheol (Frontiers in Neurology, 2022)
Background Cerebral palsy (CP) is one of the most common causes of disability in children. It is characterized by impairment in motor function and coordination and difficulties in performing daily life activities. Previous research supports that neurologic music therapy (NMT) was effective in improving motor function, cognition, and emotional wellbeing in patients with various neurologic disorders. However, the benefit of NMT in patients with CP have not yet been thoroughly investigated. The aim of this review was to investigate the potential effect of NMT motor rehabilitation techniques for patients. Materials and methods We searched articles published up to May 24, 2022 in PubMed, Embase, Scopus, Cochrane library, Web of science, and Ovid MEDLINEdatabases. We included studies that investigated the effect of NMT in patients with CP. Results After search, 4,117 articles were identified using the search terms. After reading the titles and abstracts, 4,089 articles that did not meet our inclusion criteria were excluded. The remaining 28 articles which were assessed for eligibility. Finally, 15 studies were included in this systematic review. Among 15 studies that investigated the effect of NMT on patients with CP, 7 studies were on rhythmic auditory stimulation (RAS), 6 studies were on therapeutic instrumental music performance (TIMP), and 2 studies were on patterned sensory enhancement (PSE). Conclusions Various techniques of NMT brings beneficial effects for gross and fine motor improvements in patients with CP. NMT techniques, such as RAS, TIMP, and PSE, may be a potential alternative rehabilitation strategy to enhance gross and fine motor skills for patients with CP.